Case Report: A tortuous diagnosis and successful multimodal treatment of thyroid follicular carcinoma with pelvic metastasis - Hong, Zhi-Liang; Huang, Hai-Jian; Chen, Sheng; Yang, Jian-Chuan; Wu, Song-Song (Frontiers in Oncology, 2023)
Purpose To provide reference method for the treatment of thyroid follicular carcinoma by studing the clinical imaging, pathological features and multimodal treatment of a case of thyroid follicular carcinoma with bone metastasis. Methods By identifying the case’s clinical, imaging, pathological features of a case of thyroid follicular carcinoma with bone metastasis, reflecting on the case’s diagnosis and treatment process, and referring to literature about the characteristics of thyroid follicular carcinoma, the study aims to provide reference for the treatment of this kind of disease. Result A 67-year-old male patient was admitted to the hospital with clinical symptoms of left pelvic pain. The biopsy pathology showed well-differentiated thyroid tissue. Considering his medical history, conclusion of thyroid follicular carcinoma metastasis could be made.The patient was stable and no tumor progression was observed after a combination of therapies including 131I and topical and targeted agents. Conclusions Thyroid follicular carcinoma are prone to bone metastasis, and bone metastasis is the first symptom in some cases. Clinical imaging and pathology are needed for correct diagnosis, and a successful treatment requires a combination of multiple approaches including 131I, which is a Radioactive Iodine Therapy(RAI), local therapy and targeted drug therapy.